1997
DOI: 10.1007/s004390050394
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-haplotype analysis of steroid 21-hydroxylase (CYP21) deficiency in Finland. Implications for the population history of defective alleles

Abstract: Congenital adrenal hyperplasia (CAH) due to steroid 21-hydroxylase deficiency is a common inherited defect of adrenal steroid hormone biosynthesis. Unusually for genetic disorders, the majority of mutations causing CAH apparently result from recombinations between the CYP21 gene encoding the 21-hydroxylase enzyme and the closely linked, highly homologous pseudogene CYP21P. The CYP21 and CYP21P genes are located in the major histocompatibility complex class III region on chromosome 6p21.3. We analyzed the mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
3
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 57 publications
2
48
3
2
Order By: Relevance
“…61 Of the chimeras, CH-7 was first identified in a Czech population and represents the most frequent allele. 20 Thus, knowledge about the ethnic diversity and specificity of the CYP21A2 mutations might help guide clinicians toward a diagnosis of 21-OHD prior to molecular testing.…”
Section: Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Of the chimeras, CH-7 was first identified in a Czech population and represents the most frequent allele. 20 Thus, knowledge about the ethnic diversity and specificity of the CYP21A2 mutations might help guide clinicians toward a diagnosis of 21-OHD prior to molecular testing.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…59 One study found at least half of all patients with 21-OHD in Finland were due to 3 most common founder mutation-haplotypes, and only one-sixth of the haplotypes represented single cases. 61 Of the chimeras, CH-7 was first identified in a Czech population and represents the most frequent allele. 20 Thus, knowledge about the ethnic diversity and specificity of the CYP21A2 mutations might help guide clinicians toward a diagnosis of 21-OHD prior to molecular testing.…”
Section: Population Genetics and Ethnic Diversity Of Cyp21a2 Genotypesmentioning
confidence: 99%
“…There have been various studies (White et al 1988;Sinnott et al 1990;Levo and Partanen 1997;Koppens et al 2000) indicating hybrid genes with the 30-kb deletion between CYP21P and CYP21 genes in Caucasians. Several studies (Lee et al 2002;Lee et al 2003a) have shown that there are three distinct chimeric CYP21P/CYP21s in the CYP21 gene in the ethnic Chinese population in Taiwan.…”
Section: Types Of Chimeric Cyp21p/cyp21mentioning
confidence: 99%
“…However, the population frequency is dependent on the population studied (White and Speiser 2000). Three reports (Levo and Partanen 1997;Koppens et al 2000;L'Allemand et al 2000) pointed out that such a gross 30-kb deletion consisted of a fused CYP21 gene, with its 5' and 3' ends corresponding to CYP21P and CYP21 respectively, and the product appearing as a 3.2-kb Taq I fragment in Southern blot analysis. In a recent study (Lee et al 2003a), it demonstrated that such a 30-kb gene deletion in fact is a chimeric CYP21P/CYP21 formation caused by multiple gene deletions, including XA, RP2, and C4B, and between unequal parts of the CYP21P and CYP21 genes in the C4-CYP21 repeat module (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…They vary among different populations. 8,17,18,22,[26][27][28][29][30][31][32][33][34][35][36][37] However, information on the variability of the CYP21P pseudogene, especially in association with the TaqI/BglII haplotypes that define the overall structure of the region, is rather limited. 18,38 Such information is highly relevant to the hypotheses describing the origin of the different categories of disease-causing mutations in CYP21: the location of crossover sites and the extent of conversion zones depend on the composition of the CYP21P gene involved.…”
Section: Introductionmentioning
confidence: 99%